Photo of Jerome Downey holding the book "Jerome: Just One More Song" - Bennett, Margaret (2012)
Photo of singer Jerome Downey at the age of 90 holding Margaret Bennett's book "Jerome: Just One More Song: Local, Social & Political History in the Repertoire of a Newfoundland-Irish Singer"